Unlocking Citizen Developer Potential: A Systematic Review and Model for Digital Transformation - Shakeel Muhammad; Victor Prybutok; Vikas Sinha (Encyclopedia)
Citizen developers, individuals outside formal IT departments who create applications using low-code/no-code platforms, are becoming increasingly pivotal as organizations navigate digital transformation. The driving force behind this paradigm shift stems from an exponentially growing demand for software solutions that consistently outpaces traditional IT departments’ capacity. Consequently, companies are turning their attention toward citizen developers, entrusting them with crafting solutions. In this work, we perform a systematic review of the existing literature to unearth the pivotal themes and subthemes and identify the factors contributing to citizen developers’ effectiveness. Our systematic review revealed a significant gap in scholarly understanding of factors contributing to citizen developers’ effectiveness. While some studies touched on these factors, none explored them comprehensively or provided an integrated framework for understanding their interrelationships. To fill this void, we propose a conceptual model to advance the understanding of the factors that influence the effectiveness of citizen developers in creating applications. While the model contributes to the theoretical understanding of citizen development, practical implications further reinforce its value. By leveraging the model, organizations can make informed decisions to enhance the productivity of citizen developers, align digital transformation strategies, and foster innovation.